A Deletion Mutation in TMEM38B Associated with Autosomal Recessive Osteogenesis Imperfecta. Issue 4 (20th March 2013) - Volodarsky, Michael; Markus, Barak; Cohen, Idan; Staretz‐Chacham, Orna; Flusser, Hagit; Landau, Daniella; Shelef, Ilan; Langer, Yshaia; Birk, Ohad S.
<x xml:space="preserve">Abstract</x> We demonstrate through homozygosity mapping and whole exome seuquencing that autosomal recessive osteogensis imperfecta (OI) type IV is associated with a homozygous deletion mutation of exon 4 of TMEM38B. TMEM38B encodes TRIC‐B, a ubiquitous component of TRIC, a monovalent cation‐specific channel involved in Ca2+ release from intracellular stores that has been shown to act in cell differentiation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>